National culture and international accounting standards in banking industry: is there an influence on credit risk? - Lopes, A.I. (Comunicaciones presentadas - Actas del XVIII Congreso AECA, 2015)
Researchers, regulators and accounting standard setters have been examining several kinds of behavior in the banking industry using loan loss provisions as a proxy for credit risk. Using European and Asian banks, this paper investigates how differences in culture across countries can affect bank risk-taken. Findings suggest that culture is an important determinant to be considered when analyzing risk factors, but not for all scores. International Financial Reporting Standards (IFRS) are also suggested as having an important role moderating the influence of culture on the treatment of expected losses.